PENGARUH PENGGUNAAN MEDIA AUDIOVISUAL TERHADAP KEMAMPUAN MENULIS KARANGAN MAHASISWA TINGKAT II PENDIDIKAN BAHASA JEPANG FKIP UNRI - Telly River Manurung; Hadriana Hadriana; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this research was to find out is there any significant effect of using audiovisual media toward essay writing ability on the Japanese students level II FKIP university of Riau. The research was experimental research which used one group pretest posttest design. The object of this research was Japanese students level II class B of FKIP university of Riau consisting of 30 students on experiment class. The technique sampling of this research was purposive sampling and the technique collecting data was test. The given tests were Japanese essay writing assessment about My Town or watashi no machi. This research used two of test were pretest and posttest. To analyze the data the researcher used SPSS 22 version. Based on data analysis, for average of students’ pretest was 55 and the average of students’ posttest increased amount 25.1 to be 80.1. it show that there is significant effect of using audiovisual media toward students Japanese essay writing ability on the students level II of Japanese education department of Riau university.Key Words: sakubun , audiovisual , writing ability